ONLINE BOOKING ACCOMMODATION IN RURAL TOURISM: AN UTAUT PERSPECTIVE - Kraguljac, Vladimir; Seočanac, Marijana; Senić, Vladimir; Dimitrovski, Darko (Economics of Agriculture, 2022)
The paper investigates the most important factors that cause tourists to intend or to already use a website for booking accommodation in rural areas of the Republic of Serbia. On a sample of 212 respondents who had previously used websites to book accommodation in rural tourism, using a modified model of acceptance and use of technology (UTAUT), the impact of four predictor variables (expected impact, expected effort, social impact and facilitation conditions) on the intention of tourists to use, and two independent variables (facilitating conditions and intentions of tourists) on the use of websites for booking accommodation in rural households in Serbia was examined. The SPSS software package was used for data analysis, using descriptive statistics and standard multiple regression. The conducted research indicates that the expected effect and facilitating conditions have a positive influence on the intention of tourists to use websites for booking accommodation, as well as that facilitating conditions and intentions of tourists have a positive impact on the use of websites when booking accommodation.